Acute vs chronic exposure to high fat diet leads to distinct regulation of PKA. (July 2017) - London, Edra; Nesterova, Maria; Stratakis, Constantine A
Abstract : The cAMP-dependent protein kinase (PKA) is an essential regulator of lipid and glucose metabolism that plays a critical role in energy homeostasis. The impact of diet on PKA signaling has not been defined, although perturbations in individual PKA subunits are associated with changes in adiposity, physical activity and energy intake in mice and humans. We hypothesized that a high fat diet (HFD) would elicit peripheral and central alterations in the PKA system that would differ depending on length of exposure to HFD; these differences could protect against or promote diet-induced obesity (DIO). 12-week-old C57Bl/6J mice were randomly assigned to a regular diet or HFD and weighed weekly throughout the feeding studies (4 days, 14 weeks; respectively), and during killing. PKA activity and subunit expression were measured in liver, gonadal adipose tissue (AT) and brain. Acute HFD-feeding suppressed basal hepatic PKA activity. In contrast, hepatic and hypothalamic PKA activities were significantly increased after chronic HFD-feeding. Changes in AT were more subtle, and overall, altered PKA regulation in response to chronic HFD exposure was more profound in female mice. The suppression of hepatic PKA activity after 4 day HFD-feeding was indicative of a protective peripheral effect against obesity in the context of overnutrition. In response to chronic HFD-feeding, and with the development of DIO, dysregulated hepatic and hypothalamic PKA signaling was a signature of obesity that is likely to promote further metabolic dysfunction in mice.